2016
DOI: 10.1615/intjmedmushrooms.v18.i5.50
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Water-Soluble Metabolites in Medicinal Mushrooms Using Proton NMR Spectroscopy

Abstract: ABSTRACT:The water-soluble metabolites in 5 mushrooms were identified and quantified using proton nuclear magnetic resonance (NMR) spectroscopy and software for targeted metabolite detection and quantification. In total, 35 compounds were found in Agaricus brasiliensis, 25 in Taiwanofungus camphoratus, 23 in Ganoderma lucidum (Taiwan) and Lentinus edodes, and 16 in G. lucidum (China). Total amounts of all identified metabolites in A. brasiliensis, T. camphoratus, G. lucidum, G. lucidum (China), and L. edodes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These data confirmed high metabolite variance in each fungal species studied, which can be used to predict their nutritional properties and nutraceutical potential. Similar results on high metabolite variance have been reported in medicinal and edible foods consumed in distinct parts of the world [6,9] …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These data confirmed high metabolite variance in each fungal species studied, which can be used to predict their nutritional properties and nutraceutical potential. Similar results on high metabolite variance have been reported in medicinal and edible foods consumed in distinct parts of the world [6,9] …”
Section: Resultssupporting
confidence: 81%
“…These data strongly suggested that these fungi may be safe for diabetics, considering that low levels of reducing sugars are unable to increase glycemic index. Interestingly, the 1 H‐NMR metabolite profiling of five Asian medicinal mushrooms such as Agaricus brasiliensis , Taiwanofungus camphoratus , Ganoderma lucidum (from Taiwan) G. lucidum (from China) and Lentinus edodes revealed the presence of free amino acids and their derivatives, carbohydrates, carboxylic acids, and nucleosides [9] . Comparable results were obtained by Liu et al [6] .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The aqueous supernatant of A . bisporus was reported to contain amino acids and carbohydrates, monomers of chitin, glucan and proteins (Lo et al ., 2016); In total, up to 10% of A . bisporus cell walls consist of proteins (Novaes‐Ledieu and Mendoza, 1981; Mendoza et al ., 1996) and thus represent a quantitatively attractive resource containing both C and N. All our isolates possessed an almost identical set of peptidase genes.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, up to 80% of the Agaricus bisporus cell wall was previously described as carbohydrates containing glucose, N‐acetylglucosamine and glucosamine, and up to 10% proteins and 10% lipids (Novaes‐Ledieu and Mendoza, 1981; Mendoza et al ., 1996). In addition to this polymeric fraction of biomass, the water‐soluble content of the closely related Agaricus brasiliensis was reported to contain a high amount of amino acids and its derivatives followed by carbohydrates, with the most abundant individual compounds being mannitol, trehalose, glucose and arabinitol (Lo et al ., 2016). Of those, mannitol was most abundant, being an energy reserve of the fungus (Hammond and Nichols, 1975).…”
Section: Introductionmentioning
confidence: 99%